Residual stand damage caused by logging operations in secondary forest in Berau District, East Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Ruslim Y, Sari DR, Kristiningrum R, Purwanti E, Utami WS, Ashari S, Leonika F. 2025. Residual stand damage caused by logging operations in secondary forest in Berau District, East Kalimantan, Indonesia. Biodiversitas 26: 2148-2156. In Indonesia, selective logging now mainly occurs on logged-over forests following the second rotation. Yet, information is lacking on the impacts of logging operation in these secondary forests. This study aims to determine the impacts of logging operations, particularly tree felling and log skidding, on residual stands in secondary forest and to see the relationship between felling intensity and stand damage and forest opening. This study was conducted in a logging concession in Berau District, East Kalimantan Province, Indonesia. To determine changes in stand structure before and after harvesting, 6 plots of 100x100 m were established. After felling and skidding, an inventory was conducted to record the number of damaged trees and the type of damage. The result revealed that with harvesting intensity averaged 11 trees per hectare, it caused residual stand damage due to felling and skidding of 17.85% and 16.62%, respectively. The most common type of damage after tree felling was broken trees, with an average of 19 trees ha-1, and the main damage during the skidding process was collapsed/tilted trees, with an average of 28 trees ha-1. In addition, it was found that the average opening of skid roads after the harvesting process was 13.26%. We suggest mitigation strategies including planning the skid road before harvesting, opening the skid road before felling, limiting the number of trees felled per hectare, implementing directional felling, and extending the maximum winching.
Keywords: Felling intensity, forest opening, logged-over forest, skid road, stand damage